AN INTERDISCIPLINARY EPISTEMOLOGY OF DIGITAL ETHICS FOR SHAPING GENERATION Z MORALITY IN ISLAMIC EDUCATION - Umi Khofifah, Intan; Khanifah, Rizky Nur; Romadhon, Rohmat Ilham (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Purpose:  This study formulates a digital ethics epistemology within Islamic education to shape the morality of Generation Z as digital natives facing challenges such as cyberbullying, disinformation, and identity crises due to filter bubbles, exacerbated by the dichotomy between religious knowledge (normativity) and general knowledge (historicity and empiricism). Method: Employing a qualitative-philosophical approach based on content analysis and an integrative-interconnective framework. The research explicitly integrates interdisciplinary sources: (1) Qur’anic verses along with classical tafsirs (Tafsir Ibn Kathir and Tafsir Al-Mishbah); (2) contemporary epistemological philosophy literature (concepts of truth, justification, and epistemic vices); and (3) empirical scientific studies on social media algorithms, big data, digital psychology, and philosophy of technology. Result: The main result is an Islamic education model based on three pillars: Qur’anic normativity (e.g., the principle of qaulan sadīdan in Q.S. An-Nisa’: 9), philosophical rationality, and scientific empiricism. Conclusion: The primary theoretical contribution is the formulation of a digital ethics epistemological framework that transcends conventional normative approaches, fostering digital epistemic awareness in Generation Z—the ability to distinguish between haq and batil while acting ethically responsible in virtual spaces—thus producing robust digital integrity for Muslim youth in the digital era.